Survei Tingkat Kebugaran Jasmani Peserta Didik Fase C di SD Negeri Dukuh II Kecamatan Ngadiluwih - Fitria Arba'Ina; Rendhitya Prima Putra; Wing Prasetya Kurniawan (Jurnal Ilmiah Mandala Education, 2026)
Physical fitness is one of the main indicators of students' health quality, and it gets special attention in phase C (grades V and VI) because it coincides with a period of rapid physical and motor development. This study aims to find out the level of physical fitness of phase C students at SD Negeri Dukuh II, Ngadiluwih District, using the Indonesian Student Fitness Test (TKSI) instrument. The study used a quantitative approach with a descriptive survey design. The entire population of 35 students was used as a sample through total sampling, consisting of 19 boys and 16 girls. Data was collected through five TKSI test components, namely Child Ball (coordination), Tok-Tok Ball (accuracy), Move The Ball (abdominal muscle strength), Shuttle Run 8×10 m (agility), and 600-meter run (cardiorespiratory endurance), then analyzed using T-Score and Norm-Referenced Assessment (PAN).The research results show that the physical fitness level of male students falls into the categories of very good 5.26%, good 21.05%, fair 47.36%, poor 15.79%, and very poor 10.53%; while female students fall into the categories of very good 0%, good 31.25%, fair 37.50%, poor 25%, and very poor 6.25%. Overall, the physical fitness of phase C students at SD Negeri Dukuh II, both boys and girls, is generally in the fair category, so more directed and continuous physical activity development is needed.